Development of Artistic Perception of Epic Work by the Students of Philological Faculty in the Process of Study of Ukrainian Literature - Dorosh, Galina (Pedagogical Discourse, 2012)
The article investigates the formation of artistic perception of epic work by the students of philological faculty in the process of study of Ukrainian literature